Comprehensive Approach to the Treatment of Retinopathy in Malignant Arterial Hypertension: Clinical Data (American Journal of Pediatric Medicine and Health Sciences (2993-2149), 2025)
Malignant arterial hypertension (MAH) is associated with target organ damage, including the retina, leading to the development of hypertensive retinopathy. This condition is characterized by edema, hemorrhages, ischemia, and impairment of the visual analyzer function. A comprehensive approach, including pharmacotherapy, risk factor correction, and retinal monitoring, plays a key role in the treatment of these patients.